Methyl jasmonate delays the browning of litchi pericarp by activating the phenylpropanoid metabolism during cold storage - He, Meiying; Yin, Feilong; Pak Dek, Mohd Sabri; Liao, Lingyan; Liu, Yunfen; Liang, Yuanli; Cai, Wen; Huang, Liangliang; Shuai, Liang (Elsevier B.V., 2025)
The market value of litchi fruit decreases due to pericarp browning. Methyl jasmonate (MeJA) has the ability to inhibit the occurrence of browning in litchi pericarp after harvest. However, the molecular mechanism underlying this effect remains unknown. In the present study, we used 100 μM MeJA to treat the ‘Guiwei’ litchi fruit to investigate the molecular mechanism by which MeJA delays the occurrence of browning via the phenylpropanoid metabolism. The results demonstrated that MeJA treatment effectively decreased the accumulation of reactive oxygen species (ROS), relative leakage rate (Rlr), and malondialdehyde (MDA) content. Additionally, MeJA treatment enhanced the enzyme activities of phenylalanine ammonia-lyase (PAL), cinnamate-4-monooxygenase (C4H), and 4-coumarate: coenzyme A ligase (4CL) in the early stage of phenylpropanoid metabolism, and up-regulated the expression of their respective genes, resulting in an increased content of GC, EGC, EGCG, EC, ECG, CG, total phenolics and flavonoids that help eliminate excess ROS and maintain a high antioxidant capacity. Treatment of fruit with MeJA down-regulated the gene expression and enzyme activity of peroxidase (POD) and decelerated the decline in the content of anthocyanins. Interestingly, MeJA treatment induced both the activity and gene expression of polyphenol oxidase (PPO). Correlation analysis showed that pericarp browning is closely related to PAL, C4H, 4CL, and phenolic components. In conclusion, MeJA treatment activated the early stage of the phenylpropanoid metabolism pathway, enhanced antioxidant capacity, and maintained anthocyanins content in the pericarp, thus delaying the browning of litchi fruit during storage at 4 ℃. These findings will lay the foundation for the application of MeJA in fruit preservation.